The legitimation of the presence of Bolivian migrants in Argentina in the the National Directorate of Migrations discourse - Flax, Rocío (2022)
This paper is part of research on social representations about migrants in the political, legal and institutional discourse in Argentina and aims to analyze the book Nosotros, los que vinieron (Vol. 2), issued by the National Directorate of Migrations (DNM) in 2015.  First, we contextualize the publication, making a survey of paratextual modifications of Vol. 1 and analysis of the selection of interviewed subjects according to different social variables. In second place we analyze two of the life stories in Vol. 2, selected because they dwell on enslavement and forced work. Our aim is to determine how the DNM deals with these cases of slave labor. We conclude that DNM minimize the gravity of the narrated facts, avoids labeling as crimes and romanticize the traumatic experiences, considering them as stones in the road to a better life the protagonist faced. We inscribe our research in Critical Discourse Analysis.